Ionized gas outflows in the interacting radio galaxy 4C +29.30. Issue Volume 15:Issue S359(2020) (March 2019) - Couto, Guilherme S.; Storchi-Bergmann, Thaisa; Siemiginowska, Aneta; Riffel, Rogemar A.
Abstract: We investigate the ionized gas excitation and kinematics in the inner 4.3 × 6.2 kpc 2 of the merger radio galaxy 4C +29.30. Using optical integral field spectroscopy with the Gemini North Telescope, we find signatures of gas outflows, including high blueshifts of up to ∼−650 km s −1 observed in a region ∼1″ south of the nucleus, which also presents high velocity dispersion (∼250 km s −1 ). A possible redshifted counterpart is observed north from the nucleus. We propose that these regions correspond to a bipolar outflow possibly due to the interaction of the radio jet with the ambient gas. We estimate a total ionized gas mass outflow rate of \[M_out = 18.1arrayc + 8.2 - 5.3array1pt 1pt \] with a kinetic power of \[E = 5.8arrayc + 7.6 - 2.9array × 10^421pt 1pt \], which represents \[3.9arrayc + 5.1 - 1.5array% \] of the AGN bolometric luminosity. These values are higher than usually observed in nearby active galaxies and could imply a significant impact of the outflows on the evolution of the host galaxy.